The Coinsurance Effect of Corporate Diversification An Empirical Analysis of the Accounting and Economic Implications - Nußmann, Dominik (Quantitatives Controlling, 2018)
Dominik Nußmann comprehensively analyzes the coinsurance effect of corporate diversification by first providing a structured review of all relevant findings presented in the financial economics and accounting literature. Based on this review, he examines important accounting and economic implications of the coinsurance effect by means of two comprehensive empirical analyses. In particular, he finds that diversified firms benefit from coinsurance through financial as well as accounting synergies which entail considerable value-enhancing potentials. Contents The Firm Characteristic of Corporate Diversification Corporate Diversification and Earnings Quality Implication for the Excess Value of Corporate Diversification Target Groups Academics and students in the fields of finance and accounting Professional capital market investors, corporate manage rs, and anyone interested in the implications of corporate diversification The Author Dr. Dominik Nußmann received his doctoral degree from the University of Cologne under the supervision of Prof. Dr. Carsten Homburg (Department of Business Administration and Management Accounting). .